2011
DOI: 10.1038/jcbfm.2011.15
|View full text |Cite
|
Sign up to set email alerts
|

Crossed cerebellar diaschisis after stroke: Can perfusion-weighted MRI show functional inactivation?

Abstract: In this study, we aimed to assess the detection of crossed cerebellar diaschisis (CCD) following stroke by perfusion-weighted magnetic resonance imaging (PW-MRI) in comparison with positron emission tomography (PET). Both PW-MRI and 15O-water-PET were performed in acute and subacute hemispheric stroke patients. The degree of CCD was defined by regions of interest placed in the cerebellar hemispheres ipsilateral (I) and contralateral (C) to the supratentorial lesion. An asymmetry index (AI = C/I) was calculated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 28 publications
2
24
1
Order By: Relevance
“…Moreover, we enrolled a large patient cohort which exceeded the size of study populations investigated in terms of CCD so far (mean: 51.1; range: 18-113). 13,14,17,22,25,26,28,52 Still, we cannot fully rule out the possibility of having underestimated the frequency of CCD as we counted only those cases as CCD positive, that show hemodynamic alterations suggestive of CCD in at least two perfusion parameter maps. However, artifacts on single perfusion maps can often be observed in CT imaging of the posterior fossa and this approach helped to limit the number of false-positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we enrolled a large patient cohort which exceeded the size of study populations investigated in terms of CCD so far (mean: 51.1; range: 18-113). 13,14,17,22,25,26,28,52 Still, we cannot fully rule out the possibility of having underestimated the frequency of CCD as we counted only those cases as CCD positive, that show hemodynamic alterations suggestive of CCD in at least two perfusion parameter maps. However, artifacts on single perfusion maps can often be observed in CT imaging of the posterior fossa and this approach helped to limit the number of false-positive findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, another study reported that DSC MR perfusion at 1.5T was not suited to show CCD after stroke because of poor accuracy compared with that of PET. 21 Recently, arterial spin-labeling (ASL) was introduced as a noninvasive method for assessing cerebral hemodynamics. This method uses endogenous arterial water as a freely diffusible tracer labeled by radiofrequency pulses.…”
mentioning
confidence: 99%
“…These findings are consistent with previous studies that have reported metabolic changes of CCD, which also reported hemodynamic changes. [4][5][6] However, we cannot exclude an influence of hyperoxia-induced change in CBF and CBV, on the OCI results, since hyperoxia precipitates a decrease in CBF and CBV in healthy tissue, which may reduce T2*-weighted signal intensity. However, any influence of hemodynamic changes after respiratory challenge on the T2*-weighted signal has been shown to be relatively small, if present.…”
Section: Discussionmentioning
confidence: 92%
“…3 PET is the gold standard technique used to show CCD, and few studies have used magnetic resonance (MR) imaging to show the hemodynamic changes associated with the phenomenon. [4][5][6] Madai et al 6 showed that although reduced cerebral blood flow (CBF) and cerebral blood volume (CBV) may be seen with MR perfusion (MRP), perfusion maps did not reliably reflect the degree of CCD.…”
Section: Introductionmentioning
confidence: 99%